Expression of the MRP2 gene-encoded conjugate export pump in human kidney proximal tubules and in renal cell carcinoma - Schaub, Thomas P.; Kartenbeck, Jürgen; König, Jörg; Spring, Herbert; Keppler, Dietrich (Journal of the American Society of Nephrology, 1999)
Abstract. Human kidney proximal tubule epithelia express the ATP-dependent export pump for anionic conjugates encoded by the MRP2 (cMRP/cMOAT) gene (symbol ABCC2). MRP2, the apical isoform of the multidrug resistance protein, is an integral membrane glycoprotein with a molecular mass of approximately 190 kD that was originally cloned from liver and localized to the canalicular (apical) membrane domain of hepatocytes. In this study, MRP2 was detected in human kidney cortex by reverse transcription-PCR followed by sequencing of a 826-bp cDNA fragment and by immunoblotting using two different antibodies. Human MRP2 was localized to the apical brush-border membrane domain of proximal tubules by double and triple immunofluorescence microscopy including laser scanning microscopy. - The expression of MRP2 in renal cell carcinoma was studied by reverse transcription-PCR and immunoblotting in samples from patients undergoing tumor-nephrectomy without prior chemotherapy. Clear-cell carcinomas, originating from the proximal tubule epithelium, expressed MRP2 in 95% (18 of 19) of cases. Immunofluorescence microscopy of MRP2 in clear-cell carcinoma showed a lack of a distinct apical-to-basolateral tumor cell polarity and an additional localization of MRP2 on intracellular membranes. MRP2, the first cloned ATP-dependent export pump for anionic conjugates detected in human kidney, may be involved in renal excretion of various anionic endogenous substances, xenobiotics, and cytotoxic drugs. This conjugate-transporting ATPase encoded by the MRP2 gene has a similar substrate specificity as the multidrug resistance protein MRP1, and may contribute to the multidrug resistance of renal clear-cell carcinomas.